Numerical modeling of the sidewall losses of Pedestal waveguides - Carvalho, Daniel O. [UNESP]; Melo, Emerson G.; Alayo, Marco I. (Optica Publishing Group, 2016)
We use numerical simulations and optical characterizations of Pedestal waveguides to show that it leads to lower propagation losses than rib or strip waveguides, due essentially to the smaller sidewall roughness in these waveguides.